2018
DOI: 10.1002/ecs2.2442
|View full text |Cite
|
Sign up to set email alerts
|

Associational susceptibility of a native shrub induced by context‐dependent attraction of an invasive herbivore

Abstract: Citation: Lillian, S., R. A. Redak, and M. P. Daugherty. 2018. Associational susceptibility of a native shrub induced by context-dependent attraction of an invasive herbivore. Ecosphere 9(10):Abstract. Indirect interactions among native and invasive species are notoriously difficult to predict.Here, we apply theory from trait-mediated indirect effects and plant-insect interactions to explain the outcomes of multiple invader interactions. The present study investigates the roles of herbivore preference and plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…For example, plants may experience associational resistance when more palatable species or alternate hosts are present (Fernandez‐Conradi et al, 2018; Hahn & Orrock, 2016), when visual or olfactory cues from neighbours disrupt the ability of herbivores to locate the focal species (Finch et al, 2003; Rausher, 1981), or when the architecture or defences of neighbours deter herbivore foraging (i.e., provide an associational refuge; Coverdale et al, 2018). Conversely, plants may experience associational susceptibility (i.e., increased herbivory due to neighbours; Kim et al, 2015; Letourneau, 1995) when herbivores ‘spill over’ from neighbours to the focal plant (Lillian et al, 2018; White & Whitham, 2000), or when neighbour‐driven changes to focal plant traits increase the plant's vulnerability to herbivore attack (Castagneyrol et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, plants may experience associational resistance when more palatable species or alternate hosts are present (Fernandez‐Conradi et al, 2018; Hahn & Orrock, 2016), when visual or olfactory cues from neighbours disrupt the ability of herbivores to locate the focal species (Finch et al, 2003; Rausher, 1981), or when the architecture or defences of neighbours deter herbivore foraging (i.e., provide an associational refuge; Coverdale et al, 2018). Conversely, plants may experience associational susceptibility (i.e., increased herbivory due to neighbours; Kim et al, 2015; Letourneau, 1995) when herbivores ‘spill over’ from neighbours to the focal plant (Lillian et al, 2018; White & Whitham, 2000), or when neighbour‐driven changes to focal plant traits increase the plant's vulnerability to herbivore attack (Castagneyrol et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Herbivore‐mediated indirect effects of invasive plants on native plants are largely context‐dependent (Lau & Strauss, 2005; Lillian et al., 2018), and they can be positive (Atwater et al., 2011), neutral (White et al., 2008) or negative (Orrock et al., 2015; Rand et al., 2004; Recart et al., 2012). Exotic herbivores reassociated with exotic plants in the introduced range may damage the exotic plants more than native plants, which could tip the competitive balance in favour of the native plants.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, introduced herbivores sometimes feed on native plants and decrease their fitness and competitive ability (Louda et al., 2003; Paynter et al., 2020). Moreover, apparent competition can occur when invasive plants enhance the damage caused by the introduced herbivores to native plants (Lau & Strauss, 2005; Lillian et al., 2018; Rand et al., 2004), which reduces interspecific competition, thereby benefitting the invasive plants. This may also promote the establishment of other exotic plants, predicted by the invasional meltdown hypothesis, which states that facilitation among exotic species results in the accumulation of exotic species and their impacts (Simberloff & Von Holle, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The spillover effect has been shown to be largely dependent on site‐ and landscape‐scale abundances of the exotic plant (Rand & Louda, 2004). It has also been suggested that plant phenology and insect communities may determine the apparent competition, which makes it difficult to predict their effects (Lau & Strauss, 2005; Lillian et al, 2018; Russell & Louda, 2005). On the other hand, a study that reviewed nontarget impacts of biological control agents found that few had a negative impact on native species (Hinz et al, 2019; Suckling & Sforza, 2014).…”
Section: Introductionmentioning
confidence: 99%